Peningkatan Hasil Belajar Matematika Menggunakan Pembelajaran Numbered Heads Together - Ifa Fauziyah Farid (Sekolah Tinggi Agama Islam Pati, 2022)
Student collaboration in solving problems in learning can improve learning outcomes. In fact, most student learning outcomes still do not meet the Minimum Completeness Criteria. Therefore, learning must be able to facilitate student involvement in studying the material, share ideas with each other, and be able to consider the most appropriate answers in learning so that learning outcomes are achieved optimally. The purpose of this study was to determine the improvement of students' mathematics learning outcomes in the material of measuring angles using the Numbered Head Together learning method. This research is a classroom action research following the design of Kemmis and Mc Taggart. The research subjects were fourth grade students of SDIT Al Akhyar in semester 2 of the 2017/2018 academic year, totaling 27 students. Data collection techniques using interviews, observations, and tests. The data analysis technique used descriptive analysis techniques. The indicator of research success is achieved if eighty percent (80%) of students reach the Minimum Completeness Criteria (KKM) which is 75. The results show that the percentage of completeness of students' KKM scores is 33.33% (pre-cycle) to 76.67% (cycle I) then to 81.48% (cycle II). The test results in the second cycle showed that 81.48% of students reached the KKM so that the research could be stopped until the second cycle because it had reached the indicators of research success. This means that the Numbered Heads Together (NHT) learning model can improve students' mathematics learning outcomes.